The Role of Supervision of the Board of Commissioners in the Company PT. XYZ - Chandra, William; Wijayati, Nureni (JMKSP (Jurnal Manajemen, Kepemimpinan, dan Supervisi Pendidikan), 2024)
The importance of implementing good governance principles that do not just focus on formality, but on substance for public companies is important. This research aims to of paying more attention to corporate governance in the context of the ASEAN Corporate Governance Scorecard. The method used in this research uses a qualitative approach. the research results found that a focus on board diversification, meeting minutes, appointment of a corporate secretary, and evaluation of board performance can provide a strong foundation for increasing transparency, accountability, and corporate resilience amidst ever-evolving business dynamics. Emphasis on the inclusion of independent commissioners, the formation of special board committees, and the introduction of best governance practices are also important in facing regulatory changes and industry dynamics.